A novel approach of automatically designing EDM electrodes for machining uncut regions. Issue 4 (4th July 2018) - Geng, Weizhong; Liu, Haojie
ABSTRACT: With the restriction of the diameter and feed direction of the cutting tool in milling process, electric discharge machining (EDM) is the only effective machining technology for the uncut regions with internal sharp corner. Automatic design of the electrode is of great significance for the CAD/CAM integration of EDM technology. In current CAD/CAM system the electrode design is done manually by technologists based on experience and knowledge. The procedure is tedious and time-consuming. In this paper, a novel approach is proposed to automatically generate the electrode CAD model taking the topological vertices of uncut region as the hint. The hint feature points are innovatively defined and classified into three types: internal-sharp points, cutting-into points and interacting points. Based on this, our approach firstly determines the faces and the type of uncut region. Secondly, the interacting region is decomposed into the isolated region by reconstructing the topological structure, patching the split face and partitioning the shared face. Thirdly, the modeling parameters are extracted from the isolated region. Finally, the electrode CAD model is created by executing a set of generic modeling operations. The electrode CAD model can be directly used in the process planning, so as to promote the integration of CAD and CAM. GRAPHICAL ABSTRACT: